Formation and mobilization of methylmercury across natural and experimental sulfur deposition gradients. (August 2020) - Åkerblom, Staffan; Nilsson, Mats B.; Skyllberg, Ulf; Björn, Erik; Jonsson, Sofi; Ranneby, Bo; Bishop, Kevin
Abstract: We investigated the influence of sulfate (SO4 2− ) deposition and concentrations on the net formation and solubility of methylmercury (MeHg) in peat soils. We used data from a natural sulfate deposition gradient running 300 km across southern Sweden to test the hypothesis posed by results from an experimental field study in northern Sweden: that increased loading of SO4 2− both increases net MeHg formation and redistributes methylmercury (MeHg) from the peat soil to its porewater. Sulfur concentrations in peat soils correlated positively with MeHg concentrations in peat porewater, along the deposition gradient similar to the response to added SO4 2− in the experimental field study. The combined results from the experimental field study and deposition gradient accentuate the multiple, distinct and interacting roles of SO4 2− deposition in the formation and redistribution of MeHg in the environment. Graphical abstract: Image 1 Highlights: Increased loadings of sulfate increases net MeHg formation and redistributes MeHg from the peat soil to its porewater. Sulfur concentrations in peat soils correlated positively with MeHg concentrations in peat porewater. DOC is important for mobilizing MeHg from peat soils.